"A geography of the soul": The displaced and the city in the work of Aleksandar Hemon. Issue 12 (3rd December 2022) - Peinado‐Abarrio, Rubén
Abstract: Bosnian‐American author Aleksandar Hemon is a self‐described diasporic writer interested in questions of identity, displacement, and exile. This article proposes an approach to the Hemonian displaced character based on two of the most influential conceptualisations of contemporary subjectivity: on the one hand, Rosi Braidotti's critical posthuman subject, a nomadic, multiple subject who embodies complexity, favours a dynamic notion of relationality, opposes the view of difference as inferiority, and embraces a situated and accountable perspective. On the other, Nicolas Bourriaud's radicant subject, a wanderer caught between an urge to connect with the other and the forces of dislocation and removal, between individuality and the standardisation enforced by globalisation, between exchange and imposition, between enrooting and uprooting. In Hemon, subject and city are essential constituents of an elaborate system—aimed at fostering bonding and building community—which has been damaged by forced migration and violence. The insistence with which the subject's process of becoming is grounded in an urban context invites a topopoetic reading of Hemon's fiction and nonfiction. The obsessive description of the war‐ravaged architecture of besieged Sarajevo turns home into what Maria Tumarkin calls a 'traumascape', a place marked by violence and loss. Meanwhile, Chicago is the non‐place that the refugee is forced to shape into a narrative space in order to build a human network and a personal infrastructure—what Hemon terms 'a geography of the soul'. Ultimately, the phenomenological approach to the sensory experiences and material practices of the displaced person reveals how their predicament adds new meanings to urban wandering and the construction and appropriation of the city from below. The human and the urban are seen as operating in a complex network of interconnections and interdependencies, generating an ongoing state of encounter that allows Hemon and his characters to feel 'placed', both physically and metaphysically.